A Work Accident; Lucky or Unlucky? - M.D., Selçuk Kuzu (International Journal of Innovative Research in Medical Science, 2017)
Foreign bodies are frequently encountered in otorhinolaryngology. Adult patients usually encounter accidents involving foreign bodies. In this case report, we present a patient of which an iron piece was accidentally inserted between the left eye and the left side of the nose while cutting marble.